The Prestige of Syarif Hidayatullah Sunan Gunung Djati in Sunda and Sunda Kalapa 15th - 16th Century - Rosidi Rido (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The perspective of prestige power draws on Machiavelli's theories of political power in The Prince and The Discourses. The Prince states that a ruler has two powers: first, an army that knows the exact state of the country, and second, an understanding of how to defend against enemy attacks. These two powers are like two sides of the same coin. In The Discourses, Machiavelli states that religion transforms rebellious people into obedient ones. Religion is an essential tool for maintaining a civilized state and achieving prosperity. Rulers must uphold religious sites and consistently perform religious duties to the best of their ability. Theoretical Framework The theoretical framework of the Prestige of Power of Syarif Hidayatullah Sunana Gunung Jati, as seen from the connotation of Ibn Taimiyah as written by Kholid, reduces the state to a means of implementing Allah's law or sharia. Islamic state leaders focus not on the creation of law, but on the implementation of sharia law as formulated by the Prophet Muhammad. As indicated in the Quran, power is symbolized by ulama and umara, Ibn Taymiyyah said, ulu al-amr, as stated by Ibn Hazm al-Andalus. Another name for ulu al-amr is khalifah, or imam, or mulk. These terms have the same meaning: those who rule or hold power. The research method was conducted in five steps. First, the heuristic historical method was used by collecting preliminary research sources and continuing with field research and literature review. Second, source criticism was conducted, both externally (authenticity and integrity) and internally, along with the differentiation of facts. External criticism involves verifying or testing the "external" aspects of historical sources, while internal criticism involves analyzing historical data through documents and historical sources. Third, interpretation and collection of facts in various relationships (Aufassung). Fourth, historical writing (historiography), which combines the two processes of operation syinthetique and syinthetiques operation. Fifth, determining the topic, namely the Prestige of Power Sunan Gunung Jati at region Sunda and Sunda Kalapa. His research findings are that, theoretically, they can make a significant contribution to national history and, more specifically, to the history of Islamic culture in Indonesia regarding the prestige of Sunan Gunung Jati's power in Tatar Sunda and Sunda Kalapa, 15th-16th centuries, and empirically, this research can be used as a reference source for the history of Islamic culture in the Middle Ages, namely the emergence of the prestige of Sunan Gunung Jati's authority in the Sunda and Sunda Kalapa regions in the 15th-16th centuries, as well as a source of historiography for the regency and city of Cirebon in setting its history.